Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.876392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP2D6 Genotype on Metoprolol Tolerance and Adverse Events in Elderly Chinese Patients With Cardiovascular Diseases

Abstract: The latest consensus has changed CYP2D6 genotyping among Chinese population, while its impact on metoprolol tolerance and adverse events in elderly Chinese patients with cardiovascular diseases remains unclear. In this study, we prospectively included elderly patients who started metoprolol treatment for cardiovascular indications. According to the latest consensus on CYP2D6 genotype-to-phenotype translation, the patients were categorized as normal, intermediate, or poor metabolizers (NMs, IMs, or PMs, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…A Dutch study by Bijl and colleagues found an 8.5 bpm decrease in HR, leading to increased risk for bradycardia, in CYP2D6 PMs taking metoprolol compared to CYP2D6 NMs (OR = 3.86, p = 0.0014) [ 25 ]. Recently, Chen and colleagues performed a prospective observational trial of metoprolol tolerance in a Han Chinese population, stratifying adverse events by CYP2D6 phenotype [ 26 ]. While few PMs were enrolled in the study, the study did find a statistically higher incidence of postural hypotension, bradycardia, asystole, and syncope in the IM group compared to the NM group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Dutch study by Bijl and colleagues found an 8.5 bpm decrease in HR, leading to increased risk for bradycardia, in CYP2D6 PMs taking metoprolol compared to CYP2D6 NMs (OR = 3.86, p = 0.0014) [ 25 ]. Recently, Chen and colleagues performed a prospective observational trial of metoprolol tolerance in a Han Chinese population, stratifying adverse events by CYP2D6 phenotype [ 26 ]. While few PMs were enrolled in the study, the study did find a statistically higher incidence of postural hypotension, bradycardia, asystole, and syncope in the IM group compared to the NM group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also noted a relationship between CYP2D6 phenotype and clinical outcomes and, in general, a decreasing function of CYP2D6 is associated with lower blood pressure (BP) [ 20 , 21 ] and a decreased heart rate (HR) [ 20 , 21 , 22 ]. Despite sound evidence on pharmacokinetic and surrogate outcomes in the literature, an association between CYP2D6 phenotype and patient-reported clinical symptoms in metoprolol users remains uncertain as studies have found both positive [ 23 , 24 , 25 , 26 ] and negative [ 27 , 28 , 29 , 30 ] associations. The Dutch Pharmacogenomics Working Group (DPWG) has published guidelines with clearly delineated recommendations for CYP2D6 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%